Multiplexed Cas9 targeting reveals genomic location effects and gRNA-based staggered breaks influencing mutation efficiency - Santiago Gisler (Nature Portfolio, 2019)
Designing effective genome engineering strategies requires an understanding of the impact that genomic locus has on CRISPR-Cas9 activity. Here the authors use TRIP integrations to profile editing outcomes genome-wide and observe that gRNA sequence influences the structure of the double strand break.